EFFECT OF COMPETENCE ON EMPLOYEE PERFORMANCE AT PT. PLN (PERSERO) RAYON SUNGGUMINASA IN GOWA REGENCY - Rizal, Samsul; sanusi, Sanusi; suriati, suriati (Perpustakaan dan Penerbitan Unismuh Makassar, 2018)
This study aims to determine the effect of Competence on Employee Performance PT.PLN (Persero) Rayon Sungguminasa. The type of research used in this research is quantitative descriptive research. The data is processed as the result of the distribution of questionnaires to employees of PT. PLN (Persero) Rayon Sungguminasa. The data processing method used by researchers is simple linear regression analysis. The sampling method is nonprobability sampling and the technique used in taking respondents is accidental sampling. The sample in this study was 54 respondents. Partial test of hypothesis (t-test) with error tolerance level 5% or 0,05. Before the regression process, first tested the research instrument (questionnaire) with the validity and reliability test and the classical assumption test. The results all meet the criteria to be forwarded at a simple linear regression analysis stage. The results of this study showed that the Competence has a positive and significant effect on Employee Performance shown through correlation coefficient value (R) of 0,697 and t count > t table at a significant level of 5% (7,007>2,006).